2016
DOI: 10.1534/g3.116.027326
|View full text |Cite
|
Sign up to set email alerts
|

Several Critical Cell Types, Tissues, and Pathways Are Implicated in Genome-Wide Association Studies for Systemic Lupus Erythematosus

Abstract: We aimed to elucidate the cell types, tissues, and pathways influenced by common variants in systemic lupus erythematosus (SLE). We applied a nonparameter enrichment statistical approach, termed SNPsea, in 181 single nucleotide polymorphisms (SNPs) that have been identified to be associated with the risk of SLE through genome-wide association studies (GWAS) in Eastern Asian and Caucasian populations, to manipulate the critical cell types, tissues, and pathways. In the two most significant cells’ findings (B ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The role of single and cluster genes in the development and pathogenesis of SLE is described [ 22 ]. Recent technological advancements such as GWAS and microarray have expanded our understanding on gene expression, including those associated with the pathogenesis of SLE [ 23 ]. The previous studies however focused on the expression signature of blood IFN- α [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of single and cluster genes in the development and pathogenesis of SLE is described [ 22 ]. Recent technological advancements such as GWAS and microarray have expanded our understanding on gene expression, including those associated with the pathogenesis of SLE [ 23 ]. The previous studies however focused on the expression signature of blood IFN- α [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of a number of antinuclear antibodies is the most prominent and well-known process, and they are used for diagnostic purposes. However, monocytes and macrophages also play a prominent role in the disease activity, which increasingly becomes a topic of research ( 53 55 ). In SLE patients, macrophages are characterized by a proinflammatory status and show an increased production of proinflammatory cytokines, such as IFNα, TNFα, and IL-6 ( 56 58 ).…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Of these DHS, 4,583 showed SLE-specific changes for H3K4me3 and 1,714 for H3K27me3 at promoter sites. At enhancer site theses numbers were 12,109 and 3,046, respectively ( 55 ). Transcription factor binding motifs analysis revealed PU.1 and CEBPB as main transcription factors related to the H3K4me3 induced genomic areas, just as seen for β-glucan-induced training ( 10 ).…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies investigating the cell-type specific expression of these risk alleles has revealed that these genes are most highly expressed in B cells, monocytes, and plasmacytoid dendritic cells [37,38]. This suggests that genetic risk factors can contribute to both B cell-intrinsic and B cell-extrinsic triggering of the disease (Figure 2).…”
Section: Genetic Risk Factors For Lupus and Their Effect On Tolerancementioning
confidence: 99%